Interaction, Stereotypes, and Performance: Evidence from South Africa - Corno, Lucia; La Ferrara, Eliana; Burns, Justine (American Economic Review, 2022)
We exploit a policy designed to randomly allocate roommates in a large South African university to investigate whether interracial interaction affects stereotypes, attitudes and performance. Using implicit association tests, we find that living with a roommate of a different race reduces White students' negative stereotypes towards Black students and increases interracial friendships. Interaction also affects academic outcomes: Black students improve their GPA, pass more exams and have lower dropout rates. This effect is not driven by roommate's ability. (JEL D91, I23, J15, O12)